Crystal structure of the engineered endolysin mtEC340M - Wang, Jee Min; Seok, Seung Hyeon; Yoon, Won Su; Kim, Ji Hun; Seo, Min Duk (Acta Crystallographica Section F: Structural Biology Communications, 2023)
Endolysins produced by bacteriophages play essential roles in the release of phage progeny by degrading the peptidoglycan layers of the bacterial cell wall. Bacteriophage-encoded endolysins have emerged as a new class of antibacterial agents to combat surging antibiotic resistance. The crystal structure of mtEC340M, an engineered endolysin EC340 from the PBEC131 phage that infects Escherichia coli, was determined. The crystal structure of mtEC340M at 2.4 A◦ resolution consists of eight α-helices and two loops. The three active residues of mtEC340M were predicted by structural comparison with peptidoglycan-degrading lysozyme.
Keywords: Anti-Bacterial Agents; Bacteriophages; Crystallography, X-Ray; Endopeptidases; Escherichia coli; Peptidoglycan; antibacterial agents; crystal structure; endolysin mtEC340M; endolysins; Gram-negative bacteria